Effect of the concentration of phenothiazine photosensitizers in antimicrobial photodynamic therapy on bone loss and the immune inflammatory response of induced periodontitis in rats - Garcia, Valdir Gouveia [UNESP]; Longo, M. [UNESP]; Gualberto Junior, E. C. [UNESP]; Bosco, Álvaro Francisco [UNESP]; Nagata, Maria José Hitomi [UNESP]; Ervolino, Edilson [UNESP]; Theodoro, Letícia Helena [UNESP] (Wiley-Blackwell, 2014)
Background and Objective: Antimicrobial therapy can suppress periodontal pathogens and increase the effectiveness of conventional mechanical treatment. The aim of this study was to assess bone loss and the immune inflammatory response of rats under the influence of two photosensitizing agents (MB and TBO) at two different concentrations in antimicrobial photodynamic therapy (aPDT), used as an adjuvant therapy in the treatment of periodontitis.Material and Methods: Periodontitis was induced in the mandibular first molars of 162 rats. The animals were divided into nine groups: G1 - scaling and root planing (SRP); G2 - SRP plus 100 mu g/mL of methylene blue (MB); G3 - SRP plus 10 mg/mL of MB; G4 - SRP plus 100 mu g/mL of toluidine blue (TBO); G5 - SRP plus 10 mg/mL of TBO; G6 - SRP plus 100 mu g/mL of MB and laser; G7 - SRP plus 10 mg/mL of MB and laser; G8 - SRP plus 100 mu g/mL of TBO and laser; and G9 - SRP plus 10 mg/mL of TBO and laser. Six animals from each group were euthanized 7, 15, or 30 d after treatment. Bone loss (BL) in the furcation region was evaluated using histomorphometric and immunohistochemical analyses to detect the receptor activator of nuclear factor-.appa B ligand (RANKL), osteoprotegerin (OPG) and tartrate-resistant acid phosphatase (TRAP).Results: There was significantly less BL in animals treated with aPDT using low concentrations of MB and TBO at 7, 15 and 30 d. Immunohistochemical analysis revealed decreased RANKL and increased OPG in the aPDT groups and decreased TRAP-positive cells in G6 and G8.Conclusions: aPDT, using low concentrations of MB and TBO, was the most effective adjuvant therapy to SRP, acting indirectly as a downregulator of the molecular mechanisms that control bone resorption in periodontitis.
Keywords: alveolar bone loss; lasers; periodontitis; photochemotherapy